Toxoplasma gondii: How fatal is it in pediatric allogeneic bone marrow transplantation setting?. Issue 1 (12th December 2019) - Komitopoulou, Anna; Goussetis, Evgenios; Oikonomopoulou, Christina; Paisiou, Anna; Kaisari, Katerina; Ioannidou, Eleni; Sipsas, Nikolaos V.; Kosmidis, Helen; Vessalas, Georgios; Peristeri, Ioulia; Kitra, Vassiliki
Abstract: Toxoplasmosis is a disease of the immunocompetent population. However, cases of toxoplasma infection associated with immunosuppression have been reported, especially the first months after transplantation. Limited data are available about toxoplasma infection, occurring even many months post‐transplant in pediatric patients with nonmalignant and malignant diseases. We report the cases of three patients with early and late disseminated toxoplasmosis and review the literature.